2018
DOI: 10.1016/j.jallcom.2017.12.276
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, optoelectronic and transport properties of single-layer Ca2N and Sr2N electrides

Abstract: Electride materials offer attractive physical properties due to their loosely bound electrons.Ca 2 N, an electride in the two-dimensional (2D) form was successfully recently synthesized.We conducted extensive first-principles calculations to explore the mechanical, electronic, optical and transport response of single-layer and free-standing Ca 2 N and Sr 2 N electrides to external strain. We show that Ca 2 N and Sr 2 N sheets present isotropic elastic properties with positive Poisson's ratios, however, they yi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…11,42,50,51 Moreover, little is known about the transport properties of these materials, with only Ca 2 N and Sr 2 N having been analyzed theoretically. 52,53…”
Section: Introductionmentioning
confidence: 99%
“…11,42,50,51 Moreover, little is known about the transport properties of these materials, with only Ca 2 N and Sr 2 N having been analyzed theoretically. 52,53…”
Section: Introductionmentioning
confidence: 99%
“…Then, Lee et al 6 successfully synthesized the electride [Ca 2 N] + $e À , which extended the electronic crystal from 0D to 2D. Particularly, researchers nd that [Ca 2 N] + $e À possesses a series of interesting properties, such as a low work function, 7 unique light polarization characteristics, 8 excellent catalytic activity, 9 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding the theoretical evaluation of optoelectronic properties of 2D materials were published previously. It was demonstrated that localization of electronic states plays a key role in determining the properties of the considered systems [ 48 ].…”
Section: Resultsmentioning
confidence: 99%